A Gröbner basis characterization for chordal comparability graphs. (January 2017) - Ohsugi, Hidefumi; Hibi, Takayuki
Abstract: In this paper, we study toric ideals associated with multichains of posets. It is shown that the comparability graph of a poset is chordal if and only if there exists a quadratic Gröbner basis of the toric ideal of the poset. Strong perfect elimination orderings of strongly chordal graphs play an important role.